2001
DOI: 10.1007/s11912-001-0059-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Associated lymphomas

Abstract: Intermediate and high-grade non-Hodgkin lymphomas (NHL) with a B-cell phenotype are AIDS-defining illnesses. The incidence of systemic NHL is over 100 times increased, primary central nervous system NHL is over 3000 times increased, and Hodgkin's disease is approximately 10 times increased in the HIV-infected population. Unusual extranodal presentations of NHL and Hodgkin's disease are seen in HIV-infected individuals. High-grade histologies are common for both NHL and Hodgkin's disease in the HIV setting. Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Double-strand DNA breaks and homologous recombination by Vpr C Nakai-Murakami et al malignancy in AIDS patients was estimated to be 60-to1000-fold higher than healthy controls (Mayer et al, 1995;Biggar et al, 1996;Straus, 2001). Although it has been thought that an impaired cellular immunity under AIDS conditions permits the development of tumorigenesis (Knowles, 2003), recent observations indicate that non-AIDS-defining malignancies, tumors found in HIV-1-positive patients who have no deteriorated cellular immunity, are frequently observed in HIV-1-positive patients (Herida et al, 2003;Burgi et al, 2005;Lim and Levine, 2005).…”
Section: Biological Relevance Of Vpr-induced Dsbs and Hr For Hiv-1 Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Double-strand DNA breaks and homologous recombination by Vpr C Nakai-Murakami et al malignancy in AIDS patients was estimated to be 60-to1000-fold higher than healthy controls (Mayer et al, 1995;Biggar et al, 1996;Straus, 2001). Although it has been thought that an impaired cellular immunity under AIDS conditions permits the development of tumorigenesis (Knowles, 2003), recent observations indicate that non-AIDS-defining malignancies, tumors found in HIV-1-positive patients who have no deteriorated cellular immunity, are frequently observed in HIV-1-positive patients (Herida et al, 2003;Burgi et al, 2005;Lim and Levine, 2005).…”
Section: Biological Relevance Of Vpr-induced Dsbs and Hr For Hiv-1 Inmentioning
confidence: 99%
“…In addition to the mechanism of viral infection, HIV-1-induced DSBs or their signals have an impact on the approaching AIDS pathogenesis, especially for cancer development. A high incidence of malignant tumors has been reported in AIDS patients (Mayer et al, 1995;Biggar et al, 1996;Straus, 2001), and recent observations have indicated that tumor development is observed even in HIV-1-positive patients who do not show any immunocompromised manifestations (Knowles, 2003). These data suggest that HIV-1 infection is by itself oncogenic (Laurence and Astrin, 1991), but the viral protein responsible for ATM activation during HIV-1 infection has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…245 Of particular recent interest has been the increased risk of lymphoma associated with organ transplantation 246 and HIV infection. 247 …”
Section: Special Situationsmentioning
confidence: 99%
“…This is a rapidly evolving area, but there are several excellent recent reviews, 245,247 and a number of case reports highlighting unusual presentations. In general, there seems to be a 3 per cent incidence of NHL in persons infected with HIV, 247 which is 60 times that of the general population in the United States.…”
Section: Hiv-associated Lymphomasmentioning
confidence: 99%
“…Intermediate and high-grade non-Hodgkin's lymphomas (NHL) with a B-cell phenotype are AIDS-defining illnesses. Unusual presentations of NHL and Hodgkin's diseases are observed in HIV-infected individuals, since the incidence of primary central nervous system NHL is over 3000 times and systemic NHL is over 100 times increased in these individuals [2].…”
Section: Introductionmentioning
confidence: 99%